The Audit Staff Assignment Problem: A Reply. - Summers, E. L. (The Accounting Review, 1974)
This article presents a reply to a comment on the study of the audit staff assignment in accounting in the U.S. There are no actual implementations of linear programming in audit staff scheduling. There are lamentably few implementations of linear programming or other quantitative decision models. There is a report of an application of linear or goal programming to audit staff scheduling or other problem. As accounting professionals the responsibility to encourage applications of the proposed models is the priority.